1996
DOI: 10.1039/cc9960000387
|View full text |Cite
|
Sign up to set email alerts
|

A facile solid phase synthesis of 2′- and 3′-aminonucleoside triphosphates

Abstract: A convenient and time-saving solid phase synthesis of different 2'and 3'-amino-functionalized nucleoside-5'-triphosphates using polymer bounded

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Thus, we synthesized 3'-modified chain terminators in the thymidine series starting from 3'-azido-3'deoxythymidine (AZT; 1) (Scheme 1). Usually polymer-bound triphenylphosphine is suitable for the reduction of azido-nucleosides into the corresponding amino-nucleosides [11] [12]. In this case, the generated phosphine imide is hydrolyzed by concentrated aqueous ammonia.…”
mentioning
confidence: 99%
“…Thus, we synthesized 3'-modified chain terminators in the thymidine series starting from 3'-azido-3'deoxythymidine (AZT; 1) (Scheme 1). Usually polymer-bound triphenylphosphine is suitable for the reduction of azido-nucleosides into the corresponding amino-nucleosides [11] [12]. In this case, the generated phosphine imide is hydrolyzed by concentrated aqueous ammonia.…”
mentioning
confidence: 99%
“…30 It has been reported that insoluble polymeric reagents can be used in large excess to complete this conversion into an alkyl azide. [32][33][34] In Polymer-supported triphenylphosphine has previously been used for the Staudinger reaction, where the conversion of an organoazide (R-N 3 ) by a tertiary phosphine produced an iminophosphorane (R 3 P=NR) that hydrolyzed to give primary amines.…”
Section: Inmentioning
confidence: 99%
“…Polymer-supported triphenylphosphine has previously been used for the Staudinger reaction, where the conversion of an organoazide (R-N 3 ) by a tertiary phosphine produced an iminophosphorane (R 3 P=NR) that hydrolyzed to give primary amines. [32][33][34] In Step E, acetyl hydrazine, in a mixture of glacial acetic acid and methanol, was used to form the acetylhydrazides (6a/b), and the final step (F) was the formation of the triazole ring by thermolysis on the GC injector. The solutions of (6a/b) in acetonitrile could be stored at 4°C -8°C but it was found that the benzodiazepine derivatives were not produced after several months of storage.…”
Section: Inmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] Among these, a liquid-phase synthesis of 5′-TPs by reaction of the oligonucleotide with 2-chloro-4H-1,3,2-benzodioxaphosphorin-4-one (salicyl phosphorochloridite) developed by Ludwig and Eckstein 10) is well known.…”
mentioning
confidence: 99%
“…4,9,11) A solid-phase adaptation of the salicyl phosphorochloridite method of Ludwig and Eckstein 10) has been developed by Schmidt et al,12) who used it to synthesize the 5′-TP of a 25-mer RNA.…”
mentioning
confidence: 99%